PENERAPAN BERMAIN PUZZLE GEOMETRI UNTUK MENINGKATKAN KOGNITIF ANAK USIA 3-4 TAHUN DI KB AL-AMIN DESA SUNGAI BESAR - Kadariah; Nisa, Uswatun; Baiti , Noor; Zulkarnaen, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve the cognitive development of children aged 3–4 years through geometric puzzle play at KB Al-Amin, Sungai Besar Village. Cognitive abilities in early childhood are essential foundations for spatial awareness and problem-solving. Initial observations indicated that children faced challenges in recognizing basic shapes and colors due to passive learning methods. This Classroom Action Research (CAR) was conducted across two cycles, each comprising planning, implementation, observation, and reflection stages. The subjects were 10 students, consisting of 6 boys and 4 girls. Data collection techniques included structured observations, interviews, and documentation. The results demonstrated a substantial improvement in children's cognitive dimensions, specifically in identifying geometric shapes, naming colors, matching sizes, and counting puzzle pieces. The percentage of classical completeness rose dramatically from the pre-action baseline to subsequent implementation phases, indicating that utilizing geometric puzzles effectively fosters an interactive, engaging, and successful cognitive learning environment in early childhood education.